Assessment of dengue mosquito breeding sources and source reduction at a coastal village in Puducherry - Venkataraman, Surendran; Sahithyaa, J.; Sugumaran, Arun (International Journal Of Community Medicine And Public Health, 2019)
Background: Dengue virus can cause a wide range of illness in humans, from unapparent infection, to classic dengue fever and to fatal dengue haemorrhagic fever. Until a vaccine becomes available for public health use, primary prevention of transmission is crucial to decrease the burden of dengue, and control of Aedes is the only available strategy. Methods: The mosquito larval survey was carried out in the month of November 2017 in Echangadu, a coastal village in Puducherry to assess mosquito breeding sources for the presence of dengue vector species. The survey was performed by selecting houses where freshwater was available. For each household, the presence or absence of possible breeding sources were recorded, as well as the presence or absence of mosquito larvae. Results: Of the 102 houses surveyed, 20 of the houses were infested with Aedes larvae. A total of 182 containers were found in these households of which 47 containers were positive for Aedes larvae. Coconut shells, plastic, metal and discarded containers were the most often found breeding sites. Conclusions: The larval surveillance indicators among the households surveyed revealed a very high risk of future dengue outbreak in the village. All the containers examined including those positive for Aedes larvae were safely disposed.